Plant Camouflage: Ecology, Evolution, and Implications. (August 2018) - Niu, Yang; Sun, Hang; Stevens, Martin
Abstract : Camouflage is a key defensive strategy in animals, and it has been used to illustrate and study evolution for 150 years. It is now evident that many camouflage concepts likely also apply to plants, attracting greatly increased attention. Here, we review the hypotheses and evidence for different camouflage strategies used by plants and conceptualise the state of play in plant concealment under a general framework of camouflage theory. In addition, we compare the camouflage strategies used by plants and animals, outline key factors promoting and constraining the evolution of concealment, and highlight the evolutionary and ecological implications of plant camouflage. Ultimately, we show how plant camouflage exhibits many commonalities with animals and how this understudied parallel phenomenon can inform key questions in ecology and evolution. Highlights: There is clear evidence that plants use camouflage as a defensive strategy. Plants use many camouflage strategies, hindering predator detection and/or recognition. Plant camouflage exhibits many ecological and evolutionary commonalities with animals. Plant camouflage is a key factor in adaptation to different habitats and population divergence. Various factors constrain and facilitate the evolution of camouflage in plants. Plant camouflage provides a novel testing ground for key questions in ecology and evolution.